HUBUNGAN ANTARA JENIS KELAMIN DENGAN SINDROMA METABOLIK SERTA KOMPONEN-KOMPONENNYA (Analisis Data Riskesdas Indonesia Tahun 2007) - , KRISNAWATY BANTAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the main cause of mortality in Indonesia is cardiovasculer disease CVD). Metabolic syndrome (MS) and each of its components (abdominal obesity, hyperglycemia, dyslipidemia, hypertension) are important factors for the development of CVD. The existence of sex difference in MS and each of its components may contribute the sex difference in the development of CVD. Studies in western countries revealed that there were misconcepts about CVD, where there was a presumption that mostly CVD was the disease of men, so that women were less affraid of this disease. Epidemiological facts showed that there was an increased in incidence of coronarry heart disease in women, doctors were slower to start the prevention therapy, to diagnosis, to refer and provide the treatment for MI condition, and fewer to investigate the CVD risk factors, in women. Public and media campaigns, made women dominantly focused on breast cancer, than CVD, even the mortality rate of CVD is greater than of breast cancer. During this time, Indonesia has not had yet a nationaly large study which evaluate the prevalence and the risk of MS and each of its components by sex. Although, sex is an unmodified risk factor for CVD, research of the prevalence and risk of MS and each of its components by sex is important due to the informations which will be obtained from this study can be useful for planning in the CVD control program based on sex Using a secondary data from âthe Riset Kesehatan Dasar Indonesia 2007â, study was conducted in 33 Provinces, consisted of 438 districts/cities in Indonesia. Cross-sectional design was used in this study. Polulation study consisted of 13.262 men and non-pregnant women, who lived in urban areas. Data were analized by using multilevel logistic regression, and the parameters in the statistical test model were estimated by software of Lisrel 87 version LisWin32. The result of the study showed that there was sex difference in the prevalence of MS and each of its compnents. The prevalence of MS, abdominal obesity, 2-hours PP hyperglycemia, HDL-hypocholesterolemia was higher among women than men. Prevalence of hypertension was higher in men than in women. There was sex difference in the risk of MS and its components. The risk of MS, and hypertension by sex was not independent, but it was modified by individual age, educational level and marital status. The risk of abdominal obesity by sex was modified by individual age, educational level and porsion of fiber consumption per capita in the household. The risk of 2-hours PP hyperglycemia by sex was modified by individual age and educational level. The risk of HDLhypocholesterolemia by sex was not modified by any other condition, women were higher at risk having HDL-hypocholesterolemia than men